2019
DOI: 10.1002/mgg3.564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the detection of GBA missense mutations and other variants using the Oxford Nanopore MinION

Abstract: Background Mutations in GBA cause Gaucher disease when biallelic and are strong risk factors for Parkinson's disease when heterozygous. GBA analysis is complicated by the nearby pseudogene. We aimed to design and validate a method for sequencing GBA using long reads. Methods We sequenced GBA on the Oxford Nanopore MinION as an 8.9 kb amplicon from 102 individuals,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 57 publications
0
48
0
Order By: Relevance
“…Therefore, genetic analysis will have to take this into account and should be performed in a specialized laboratory in order to obtain reliable results. New technologies, such as the long-read sequencer, are on the horizon for even more in-depth identification of possible GBA mutations [64].…”
Section: Pathogenetic Mutations Of the Gba Genementioning
confidence: 99%
“…Therefore, genetic analysis will have to take this into account and should be performed in a specialized laboratory in order to obtain reliable results. New technologies, such as the long-read sequencer, are on the horizon for even more in-depth identification of possible GBA mutations [64].…”
Section: Pathogenetic Mutations Of the Gba Genementioning
confidence: 99%
“…This is, for example, the case for mutations in GBA, in which heterozygous mutations increase the risk for PD and that has a neighboring pseudogene complicating the short-read alignment. Long-range PCR amplicons sequenced on the MinION were used for phased detection of SNVs and an exonic deletion [81]. More generally, in a genome-wide evaluation of loci with highly similar copies, it was also suggested that a substantial proportion of variants in genes relevant to neurodegenerative diseases cannot be assessed reliably using short reads due to issues in the alignment [82].…”
Section: Examples Of Svs In Neurodegenerationmentioning
confidence: 99%
“…While the representative physical long-read platforms such as PacBio and Oxford Nanopore sequencers produce sequences with lower base qualities than those of short-read sequencing platforms such as Illumina sequencers, this shortcoming could be circumvented when genotyping large genome aberrations, such as copy-number variants (CNVs) and SVs. This approach has been taken in various diseases [14], including cancers [1518]. Moreover, with a careful application of either the long reads alone or in tandem with a more accurate conventional short-read sequencing, single-base-level resolution aberrations such as SNVs and short indels could be genotyped.…”
Section: Cancer Genome Sequencing With Long Readsmentioning
confidence: 99%